Screening for Depression in Younger Breast Cancer Survivors: Outcomes From Use of the 9-item Patient Health Questionnaire. Issue 3 (8th February 2021) - Ganz, Patricia A; Bower, Julienne E; Partridge, Ann H; Wolff, Antonio C; Thorner, Elissa D; Joffe, Hadine; Irwin, Michael R; Petersen, Laura; Crespi, Catherine M
Abstract: Background: Major cancer organizations recommend depression screening in patients and survivors. The 9-item Patient Health Questionnaire (PHQ-9) is often suggested, with limited information about its use. Methods: Enrollment data collected from younger breast cancer survivors participating in a behavioral intervention trial were used to examine the relationship between PHQ-9 scores (range = 0-27), patient characteristics, and responses to standardized psychosocial assessment tools. Major depressive disorder criterion was met if responses to the first 2 PHQ-9 items (range = 0-6) were 3 or greater. The sample was categorized by total PHQ-9 scores: less than 5 (minimal depressive symptoms), 5-9 (mild to moderate depressive symptoms), and 10 or greater (moderate to severe depression). PHQ-9 category associations with medical, demographic, psychosocial, and behavioral characteristics were examined using analysis of variance for continuous variables and χ 2 tests for categorical variables. Results: A total of 231 women met the study prescreening eligibility criterion of mild depressive symptoms and enrolled in the study. On average, they were 45.2 years old and 2.6 years since diagnosis. At enrollment, 22.1% met the screening criterion for possible major depressive disorder; among those with PHQ-9 scores of 10 or greater, 58.3% met this criterion. Anxiety, fatigue, insomnia, and intrusive thoughts about cancer were frequent and were associated with depressive symptom severity (all P < .001). In contrast, neither demographic nor cancer treatment characteristics were associated with depressive symptoms. Conclusions: Depressive symptoms in this selected sample of younger breast cancer survivors were independent of demographic characteristics or cancer treatment history, suggesting that depression screening is necessary to detect uncontrolled depressive symptoms.